2006
DOI: 10.4141/a06-004
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality and fatty acid composition of pasture-finished beef steers fed barley and soybeans

Abstract: Duynisveld, J. L., Charmley, E. and Mir, P. 2006. Meat quality and fatty acid composition of pasture-finished beef steers fed barley and soybeans. Can. J. Anim. Sci. 86: 535-545. The effect of supplemention on the performance, carcass characteristics, meat quality, and fatty acid composition of pasture-finished cattle was studied. Thirty-two steers were assigned to four treatments in a randomized block design. Treatments were: totally mixed ration (TMR) [confinement-fed total mixed ration (60% grass silage, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…The levels of CLA observed in this experiment were slightly higher than those observed by Realini et al (2004) for grazing and confined animals and lower than those observed by Duynisveld et al (2006). Poulson et al (2004) observed similar levels of CLA to this experiment in meat (Longissimus dorsi and Semitendinosus) from feedlot Angus crossbred steers in the USA and higher than those observed for animals finished on pasture or fed pasture throughout their life.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…The levels of CLA observed in this experiment were slightly higher than those observed by Realini et al (2004) for grazing and confined animals and lower than those observed by Duynisveld et al (2006). Poulson et al (2004) observed similar levels of CLA to this experiment in meat (Longissimus dorsi and Semitendinosus) from feedlot Angus crossbred steers in the USA and higher than those observed for animals finished on pasture or fed pasture throughout their life.…”
mentioning
confidence: 56%
“…Some research indicates that in finishing systems, the SFAs present in greater quantities in bovine IMF are palmitic, stearic and myristic, respectively (Realini et al, 2004;Nuernberg et al, 2005;Garcia et al, 2008;Alfaia et al, 2009). However, there is high variability in the concentration of these FAs in different experiments and when different diets are fed (French et al, 2003;Duynisveld et al, 2006;Blanco et al, 2010;Duckett et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, energy supplementation used in the present study seems not to have been effective on ruminal biohydrogenation, since it caused no changes of the concentrations of vaccenic acid and CLA cis-9-trans-11. The production of CLA can also be related to higher intake of polyunsaturated fatty acids, especially linoleic acid (Duynisveld et al, 2006); however, the high content of this fatty acid in the concentrate fraction of the diet (Table 1) was not enough to promote changes in the CLA content in meat from animals grazing pearl millet. In grazing systems, other factors such as the proportions of leaf and stem, as well as the forage maturity, may determine the percentage of PUFA (Boufaïed et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In the current experiment, weight loss due to transportation was on average 6.8%, similar to what Arthington et al (2003) reported in weaned calves transported for 3 h. In the present study the steers needed 30 days to attain the weight previous to transportation, but Phillips et al (1987) reported shorter periods to recover pre-transportation weight. Besides of the transportation losses, when cattle are turned-out to pasture they loose weight and may need 10-18 d to recover the loss (Nams and Martin, 2007) Duynisveld et al (2006). It could be suggested that the mobility of the pasture finished steers could have decreased the energy available for growth.…”
Section: Live Weight Weight Gains and Intakementioning
confidence: 99%